Editorial - Daniel Halliday (Intergenerational Justice Review)
The intergenerational transfer of wealth and property attracts a fair amount of controversy. According to some, inheritance (at least when unregulated) is a source of arbitrary material inequality. When some inherit and others do not, the resulting inequalities are apparently due to differences in luck or circumstance. Inequalities of this sort may be harder to justify than those owed to differences in the life choices or levels of effort, such as the sorts of inequalities that might arise in a properly meritocratic labour market. A slightly different, though perhaps complementary view is that the practice of inheritance may, over time, be among the factors maintaining an objectionable class hierarchy. Again, such hierarchies might not be so profound in a society where all incomes were due to individuals’ own efforts.